Proposta de indicadores de sustentabilidade aplicada para o estudo da vulnerabilidade da comunidade do Batoque- Aquiraz /CE - Lopes, José Lidemberg de Sousa (2013)
The Resex of Batoque was created by presidential decree on 5 June 2003, and covers an area of approximately six hundred and one acres and five centiares, situated on land of navy in Aquiraz municipality, in the state of Ceara. The objective of this study was to evaluate the vulnerability of the community of Batoque, and it was found that the locality suffers pressures arising from the inadequacy of the use and occupation of the soil and lack of basic infrastructure. Applied as a methodology the following steps: a) bibliographic research related to community affairs, traditional landscape as geographical category, indicators and environmental vulnerability; (b) instruments, such as images of satellites Quickbird, scale 1:30,000, year 2008; (c) visit the public organs, where they were collected secondary data based on censuses and technical reports; (d) field visit to obtain primary data. Such procedures have facilitated the confection of cartographic materials, location fragility map of local environmental units, which it was analyzed the dynamics and functioning of each system Geoenvironmental compartment of the community. For the final result of the research, were drawn up criteria (exposure, sensitivity, and responsiveness) and inside the same were proposed 16 indicators socialenvironmental (occupation of the beach strip, the complex vegetational and plain fluviocoastal; priority areas for conservation; agricultural suitability; water quality; area in unit of conservation; soil conservation; access to water supply, garbage collection, the sanitary sewerage; rate of illiteracy; family income; waterborne diseases; unemployment rate). All these criteria and variables adopted were calculated in the form of arithmetic mean, as well as the final result - the IVSA. The proposition of these variables had the intention to analyze the degree of vulnerability of the socioenvironmental Batoque.